Pembuatan Tempat Cuci Tangan Sistem Injak Sebagai Upaya Pencegahan Covid-19 Di Desa Kalikajar - Koesuma, Sorja; Nabila, Dhia Azmi; Abdullah, Azar Rafliardi; Krismonanto, Wisnu; Arifin, Imam; Nursodik, Fajar; Pratiwi, Rizki Amalia; Susanto, Andika Dwi Cipta; Ananta, Aria Arga; Salfas, Muhammad (Prosiding University Research Colloquium, 2021)
The Covid-19 pandemic has caught the world's attention which has caused various impacts on life. The spread of the virus takes place rapidly through droplets or physical contact to encourage governments to implement policies such as washing hands activities using soap cleanly and correctly. Kalikajar village government as one of the villages that are exposed Covid-19 in Purbalingga also have appealed to the people to always washing hands with soap. However, the availability of hand washing facilities is still limited and the conditions are alarming due to the lack of community maintenance. Therefore, as a form of community service, Kuliah Kerja Nyata (KKN) of Sebelas Maret University has initiative to create washbasin based on stepping system that can be used by people to get clean and healthy living. The service implementation stages include survey and identification of partner problems, preparation of problem solving frameworks, problem solving solution programs, implementation of service programs, monitoring and evaluation. Manufacture of washbasin through the manufacturing process and framework design, painting, assembly, and testing. The washbasin is distributed in several locations in Kalikajar Village, such as the Kalikajar Village Hall Office, Baitul Ghufron Mosque, and Baitul Muslimin Mosque. The distribution activites to several locations had help from local residents, takmir mosques, and village heads Kalikajar. Through this washbasin, the UNS KKN Team hopes that the community and village government officials can develop and remind each other of the habit of washing hands so that it indirectly helps the government in preventing Covid-19 transmission in the surrounding community.